2018
DOI: 10.1002/cbin.10933
|View full text |Cite
|
Sign up to set email alerts
|

A small population of resident limb bud mesenchymal cells express few MSC‐associated markers, but the expression of these markers is increased immediately after cell culture

Abstract: Skeletal progenitors are derived from resident limb bud mesenchymal cells of the vertebrate embryos. However, it remains poorly understood if they represent stem cells, progenitors, or multipotent mesenchymal stromal cells (MSC). Derived‐MSC of different adult tissues under in vitro experimental conditions can differentiate into the same cellular lineages that are present in the limb. Here, comparing non‐cultured versus cultured mesenchymal limb bud cells, we determined the expression of MSC‐associated markers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 46 publications
0
14
0
Order By: Relevance
“…CD-1 strain pregnant mice at 10.5 days post coitum (E10.5), 11.5 days post coitum (E11.5), and 12.5 days post coitum (E12.5) were killed by CO 2 asphyxia. Embryos were removed from the uterus and handled, according to Marín-Llera and Chimal-Monroy (2018). For each experiment, a different number of pregnant mice with approximately ten embryos each was required: three-pregnant mice for each sample acquisition to determine the percentage of sSca + and sSca − subpopulations by flow cytometry (∼60 hindlimbs) and 10-to 12-pregnant mice for each experiment of subpopulations cell sorting (∼200-240 hindlimbs).…”
Section: Mice Embryo Hindlimbs Obtainingmentioning
confidence: 99%
See 1 more Smart Citation
“…CD-1 strain pregnant mice at 10.5 days post coitum (E10.5), 11.5 days post coitum (E11.5), and 12.5 days post coitum (E12.5) were killed by CO 2 asphyxia. Embryos were removed from the uterus and handled, according to Marín-Llera and Chimal-Monroy (2018). For each experiment, a different number of pregnant mice with approximately ten embryos each was required: three-pregnant mice for each sample acquisition to determine the percentage of sSca + and sSca − subpopulations by flow cytometry (∼60 hindlimbs) and 10-to 12-pregnant mice for each experiment of subpopulations cell sorting (∼200-240 hindlimbs).…”
Section: Mice Embryo Hindlimbs Obtainingmentioning
confidence: 99%
“…The MSC-associated markers (MSC-am) allow the identification of cell subpopulations. In vitro, cells acquire MSC-am and they may not represent in vivo populations (Boiret et al, 2005;Bara et al, 2014;Guimarães-Camboa et al, 2017;Marín-Llera and Chimal-Monroy, 2018). However, few works has been focus on identifying cell subpopulations without a previous culture (Jones et al, 2006;Chan et al, 2015;Reinhardt et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The existence of a distal undifferentiated zone in the limb as a source of stem/progenitor cells has been well established. It has been clearly demonstrated in vitro and in vivo that mesenchymal cells at early stages of development are capable of differentiating into different limb lineages (Ahrens et al, 1977; Akiyama et al, 2005; Marin-Llera and Chimal-Monroy, 2018), Even extra-limb lineages belonging to ectodermal and endodermal germ layers have been obtained in vitro (Jiao et al, 2012). However, it remains unclear whether the mesenchyme is composed of a collection of distinct types of stem/progenitor cells with restricted differentiation potential or of a group of equipotential cells capable of giving rise to the same cell lineages.…”
Section: Introductionmentioning
confidence: 99%
“…Detection of specific signatures of cell surface molecules, such as mesenchymal stromal cell-associated markers (MSCams), can enable the identification and study of distinct limb subpopulations at different developmental stages. In this sense, it has been demonstrated that few limb cells express different MSCams (Marin-Llera and Chimal-Monroy, 2018). Gretel Nusspaumer et al traced the ontogeny and relationships of distinct mesenchymal stromal cell populations previously reported in the mouse limb and found that the PDGFRa pos /CD51 cell population is the largest population of progenitors, containing mouse skeletal stem cell (mSSC) (CD200 pos , CD51 pos , CD90 neg , CD105 neg , and 6C3 neg ) and PαS subpopulations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation